2010
DOI: 10.1111/j.1524-4725.2010.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Block With and Without Epinephrine During Chemical Matricectomy with Phenol

Abstract: The mean anesthetic volume used in the epinephrine group (2.2 ± 0.4 mL) was significantly lower than the plain lidocaine group (3.1 ± 0.6 mL). There was no statistically significant difference in postoperative pain and recurrence rates, but duration of drainage was significantly shorter in the epinephrine group (11.1 ± 2.5 days) than in the plain lidocaine group (19.0 ± 3.8 days). CONCLUSION Digital block with epinephrine is safe in selected patients, and epinephrine helps to shorten the postoperative drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Using lidocaine with epinephrine 1 : 100,000 was associated with significantly shorter healing times compared to plain lidocaine: 11.1 days versus 19.0 days, and less anaesthetic solution was required [82]. Also ferrichloride 20% after the phenol rub shortened the healing period [83].…”
Section: Treatment Of Ingrown Toenailsmentioning
confidence: 99%
“…Using lidocaine with epinephrine 1 : 100,000 was associated with significantly shorter healing times compared to plain lidocaine: 11.1 days versus 19.0 days, and less anaesthetic solution was required [82]. Also ferrichloride 20% after the phenol rub shortened the healing period [83].…”
Section: Treatment Of Ingrown Toenailsmentioning
confidence: 99%
“…Many authors have reported safe use of lidocaine-epinephrine mixture for digital block in good number of patients. [44][45][46] They did not observe digital necrosis in any of their patients, rather there were added advantages of combining with epinephrine. Epinephrine facilitates faster onset of anesthesia, prolonged post-procedure pain relief, and lesser amount of local anesthetic required without much need of tourniquet placement to control bleeding.…”
Section: Other Advances In Nail Disorder Diagnosismentioning
confidence: 89%
“…Epinefrin içeren anestezik madde kullanımının operasyon sonrası iyileşme süresini belirgin bir şekilde kısalttığı gösterilmiştir (34).…”
Section: Fenol Uygulamalarıunclassified